Social science research in India : status, issues, and policies - Thorat, Sukhadeo; Verma, Samar; Indian Council of Social Science Research (New Delhi, India : Oxford University Press, 2017)
This volume elaborates on various dimensions of social science research in India, presenting a strong case for designing a comprehensive national social science policy which can meaningfully strengthen and promote a research ecosystem for improved public policymaking in the country. Addressing issues like lack of funding, availability of data, infrastructure and quality of research output, it will serve as a national benchmark and reference database for social sciences in India.
Copyright: Indian Council of Social Science Research.
Includes bibliographical references and index.
AAL
complimentary copy
Keywords: Social sciences -- Research -- India; India -- Social policy